2019
DOI: 10.1515/jpem-2018-0383
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dyslipidemia and factors affecting dyslipidemia in young adults with type 1 diabetes: evaluation of statin prescribing

Abstract: Background There is limited information about cardiovascular complications among young adults (YA) with type 1 diabetes mellitus (T1DM) who are transitioning from pediatric to adult care. We aimed to study the prevalence and associated factors of dyslipidemia (DLD) and statin treatment in these patients. Methods We recruited 129 YA with T1DM aged 15–25 years. In a cross-sectional analysis, the prevalence of DLD (low-density lipoprotein cholesterol [LDL-C] ≥ 100 mg/dL, high-density lipoprotein cholesterol [HDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
3
12
0
1
Order By: Relevance
“…HbA1c showed a strong and direct association with LDL-related variables in our T1DM sample ( Fig. 1 and Additional file 6: Table S5), in accordance with previous studies [33,35,[41][42][43]. Specifically, two recent studies performed in children and young adults with T1DM also showed a direct association between glycaemic control and overall dyslipidaemia [42], and LDL-cholesterol (this effect was further modified by proprotein convertase subtilisin/kexin 9 levels) [43].…”
Section: Ldl-related Parameterssupporting
confidence: 90%
See 1 more Smart Citation
“…HbA1c showed a strong and direct association with LDL-related variables in our T1DM sample ( Fig. 1 and Additional file 6: Table S5), in accordance with previous studies [33,35,[41][42][43]. Specifically, two recent studies performed in children and young adults with T1DM also showed a direct association between glycaemic control and overall dyslipidaemia [42], and LDL-cholesterol (this effect was further modified by proprotein convertase subtilisin/kexin 9 levels) [43].…”
Section: Ldl-related Parameterssupporting
confidence: 90%
“…1 and Additional file 6 : Table S5), in accordance with previous studies [ 33 , 35 , 41 43 ]. Specifically, two recent studies performed in children and young adults with T1DM also showed a direct association between glycaemic control and overall dyslipidaemia [ 42 ], and LDL-cholesterol (this effect was further modified by proprotein convertase subtilisin/kexin 9 levels) [ 43 ]. As is well known, LDL-cholesterol has been pointed out as a causal factor in the pathogenesis of atherosclerotic CVD in the general population [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…[20] In contrast, most other studies, mainly within the western populations had reported more frequencies of isolated high LDL-C abnormalities among TIDM cohorts. [15,17] The prominence of high Tg abnormalities, in the current study, may be adduced to the carbohydrate-enriched dietary patterns prevalent within the studied region, as suggested by Jaja et al [20] Some other authors had postulated the insulin deficiency state as a major factor and inferred that the high Tg status is a nidus for other lipid/lipoprotein abnormalities in T1DM. [21] Female predominance was observed among the overall dyslipidemics in the current study and among those with isolated abnormal high plasma Tg concentrations, which is in line with previous data.…”
Section: Discussionsupporting
confidence: 61%
“…[13,14] In contrast, three other studies with higher rates, were recently reported from Brazil, China and also in another study from the United States. [15][16][17] Homma et al reported 66.1% from Brazil among adults ≥ 19 years of age, Lou et al reported 65.3% from China, and Abeg et al reported 64% from the United States. [15][16][17] The disparity in frequency might partly be explained by the observed different cutoff points of lipid indices used in these various studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation